2020
DOI: 10.3390/ijms21186699
|View full text |Cite
|
Sign up to set email alerts
|

Dihydromyricetin Improves Endothelial Dysfunction in Diabetic Mice via Oxidative Stress Inhibition in a SIRT3-Dependent Manner

Abstract: Dihydromyricetin (DHY), a flavonoid component isolated from Ampelopsis grossedentata, exerts versatile pharmacological activities. However, the possible effects of DHY on diabetic vascular endothelial dysfunction have not yet been fully elucidated. In the present study, male C57BL/6 mice, wild type (WT) 129S1/SvImJ mice and sirtuin 3 (SIRT3) knockout (SIRT3-/-) mice were injected with streptozotocin (STZ, 60 mg/kg/day) for 5 consecutive days. Two weeks later, DHY were given at the doses of 250 mg/kg by gavage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…Several data has proved the protective effects of DHM against vascular function impairment; DHM ameliorated the diabetic induced vascular dysfunction as well as inhibited the development of atherosclerosis via attenuation of endothelial cell activation and damage. These beneficial vascular effects of DHM were found to be mediated via attenuation of ROS release [33][34][35][36]. Also, DHM was found to attenuate vascular iNOS/NO expression while enhances eNOS production leading to improved vascular activity [37,38].…”
Section: Discussionmentioning
confidence: 90%
“…Several data has proved the protective effects of DHM against vascular function impairment; DHM ameliorated the diabetic induced vascular dysfunction as well as inhibited the development of atherosclerosis via attenuation of endothelial cell activation and damage. These beneficial vascular effects of DHM were found to be mediated via attenuation of ROS release [33][34][35][36]. Also, DHM was found to attenuate vascular iNOS/NO expression while enhances eNOS production leading to improved vascular activity [37,38].…”
Section: Discussionmentioning
confidence: 90%
“…CAT protects cells from H 2 O 2 toxicity by participating in a biodefense system [37]. Hua et al showed that DHM improved endothelial dysfunction in diabetic mice via oxidative stress inhibition in a SIRT3-dependent manner [38]. Zhang et al showed that DHM protected HUVECs from oxidative damage induced by sodium nitroprusside by activating the PI3K/Akt/FoxO3a signaling pathway [39].…”
Section: Discussionmentioning
confidence: 99%
“…DHM can regulate the expression of target genes induced by TNF-α by suppressing NF-κB activation. 18 Thus, we explored whether DHM could suppress the inflammation and oxidative stress in the liver induced by APAP and the corresponding molecular mechanism.…”
Section: Discussionmentioning
confidence: 99%